Achievement of favorable uniform crystal size distribution of alpha-lactose monohydrate (α-LM) through swift cooling process. (April 2015) - Parimaladevi, P.; Srinivasan, K.
Highlights: Needle-like α-LM crystals preferable for DPI are obtained by this process at low S. This process also yields pyramidal crystals with uniform CSD for food industry. A transition point of individual and aggregated crystal nucleation is identified. Theoretical findings of nucleation kinetics are in-line with experimental results. Single method to crystallize α-LM for food and pharmaceutical applications reported. Abstract: The impact of initial concentration on size, morphology and nucleation kinetics of alpha-lactose monohydrate (α-LM) was investigated by adopting novel swift cooling crystallization process. The supersaturation dependent induction period estimated from the experiment were used to derive the nucleation kinetics based on the classical nucleation theory. Size and morphology of the nucleated crystals were analyzed with different initial concentrations. The lower concentration ( S = 4.51–6.99) yields individual crystals with needle and pyramidal morphologies and the higher concentration ( S = 6.99–8.14) yields aggregated crystals with fan-like morphology. The nucleation kinetics study reveals that, the transition in interfacial energy leads to the nucleation of aggregated crystals and the rate of aggregation increases with increase in concentration. Characterization analysis of the individual and aggregated crystals infers their crystalline phase purity and the form of crystallization. This method enables to produce α-LM crystals with a shorter induction period and the interfacial energy play an important role in producing good quality crystals suitable for dairy and dry powder inhaler applications at lower concentration levels (i.e., S = 4.51–6.99).